American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
Fred Korematsu, Christine Watkins and Howard Watkins Mr. Korematsu was honored for his fight against the WWII internment of Japanese-Americans